Nitrogen-loss and associated microbial communities in sediments from the Yangtze Estuary and adjacent sea - Teng, Zhenzhen; Zhen, Yu; Yu, Zhigang; Mi, Tiezhu; Cai, Tao (Frontiers in Marine Science, 2022)
Introduction Denitrification and anammox play the crucial role for N removal processes in coastal ecosystems, but the ecological distribution of denitrifying and anammox microorganisms and their N removal rates in the Yangtze Estuary and its adjacent sea are required in-depth analysis. Methods Here, we utilized high-throughput sequencing, qPCR, and 15N isotope to reveal the community structure and function of denitrifying and anammox microorganisms in the surface sediments from Yangtze Estuary and adjacent sea. Results The results suggested that the gene abundances of nirS and nirK for denitrifiers were higher than AMX 16S rRNA for anammox bacteria. The genera composition of nirS- and nirK-encoding denitrifiers communities showed different distribution patterns. Furthermore, Candidatus Anammoximicrobium dominated the anammox community, implying the anammox oxidation capacity of the other genera should be noted in marine sediments. Discussion Compared to anammox, denitrification was the dominant contributor of nitrogen removal process and contributed 73.5% on average. The sediment Chla was the key factor to regulate denitrification and anammox rates, indicating the fresh organic matter was more labile and easier to be utilized by NOx− removal processes.